Morning–evening differences of short-term maximal performance and psychological variables in female athletes - Jribi, Wafa; Bougrine, Houda; Aloui, Ali; Khalfoun, Jihen; Souissi, Nafaa; Mkacher, Wajdi; El Abed, Kais; Ben Abderrahman, Abderraouf (Frontiers in Physiology, 2024)
The aim of this study was to examine the effect of time of day on short-term maximal performance and psychological variables in young females. Fifteen active women participated in the study (age: 22 ±3 years) and completed Hooper and the POMS-F questionnaires subsequently. In a randomized order, they performed a maximum of 30 s cycling exercise at two different times of day: in the morning at 07:00 h and in the afternoon at 16:00 h with a recovery period of 48 h. The digit cancellation test, countermovement jump (CMJ), squat jump (SJ) test, and the lower quarter Y balance test were performed at the beginning and at the end of each session. Our results showed that only peak power and mean power (p<0.01) during the maximum 30 second cycling, reaching distances during the Y-balance (p < 0.05), Jump height in CMJ and SJ (p < 0.01) as well as attention, vigor, and stress scores (all p < 0.01) were higher in the afternoon than in the morning. Our results indicated a daily diurnal variation in short-term maximal performance and mood states in young athletic women with better performance observed during the afternoon.